Analisis Hukum Islam Tentang Pendistribusian Zakat Fitrah oleh Takmir Masjid At-Taqwa Terhadap Gharim yang Hutangnya untuk Lembaga - A Saiful Aziz; Subhan Subhan; Ubbadul Adzkiya' (Jurnal Iqtisad, 2021)
This study describes how the implementation of zakat fitrah management at the At-Taqwa Mosque, Pamedaran Village, Brebes Town, and to find out the analysis of Islamic law on the distribution of zakat fitrah to people who have debts to institutions. This research was conducted with a qualitative method and a descriptive approach. The conclusion of the study shows: (1) Management of zakat fitrah at the At-Taqwa Mosque begins with planning through deliberations of leaders and amil on D-3 Eid al-Fitr and carried out on D-1 Eid al-Fitr with the time of collecting zakat fitrah from after dawn prayer until before prayer Asr, then the amil calculates the amount of zakat fitrah that has been collected, then distributes it to asnaf in the At-Taqwa Mosque environment, namely asnaf indigent, poor, amil, fisabilillah and gharim. (2) The distribution of zakat fitrah carried out by the takmir of the At-Taqwa Mosque in Pamedaran Village to gharim whose debts to institutions are not in accordance with Islamic law, because what is meant by gharim according to the four schools of thought is a person who is in debt and it is an obligation for him to pay the debt, while in this case the person who is considered a gharim is only an intermediary for the debt and the real owner of the debt is the institution/mosque.